Cerebellar-cerebral circuits functional connectivity in patients with cognitive impairment after basal ganglia stroke: a pilot study - Lijun Zuo; Xinlong Lan; Yijun Zhou; Hao Liu; Yang Hu; Yongjun Wang; Yongjun Wang; Tao Liu; Zixiao Li; Zixiao Li (Frontiers in Aging Neuroscience)
IntroductionThis study aims to assess the pattern of functional connectivity (FC) between cerebellar subregions, the basal ganglia (BG), and the cortex, and explore the relationship between FC patterns and cognitive function after stroke with BG infarcts.MethodsA total of 39 stroke patients and 29 healthy controls were recruited. Four cerebellar seed points were selected, and the FC of each seed point with other voxels in the whole brain was calculated. FC and cognitive performance were compared between the two groups, and their correlations were analyzed.ResultsStroke patients exhibited increased FC between the bilateral cerebellum IX and BG (particularly the head of the caudate nucleus), which was positively correlated with episodic memory, visuospatial ability, and attention. Increased FC was also observed between the right cerebellum Crus I/II and BG, as well as the bilateral cerebellum VI and BG, correlating positively with episodic memory. Conversely, decreased FC was identified between the bilateral cerebellum IX and the right caudal cuneus, which negatively correlated with episodic memory, language, and attention but positively correlated with executive function. Additionally, increased FC between the bilateral cerebellum VI and the bilateral inferior parietal lobule was associated with improvements in episodic memory, language, and attention. Decreased FC was observed between the right cerebellum VI and the left insula, as well as between the right cerebellum Crus I/II and the left insula, which negatively correlated with episodic memory.DiscussionThe enhanced FC between the cerebellum and BG, along with the reorganization of new neural circuits involving the cerebellar cortex, may contribute to cognitive recovery following stroke. These changes may represent compensatory mechanisms of the cerebellum in response to stroke injury.